2014
DOI: 10.1261/rna.044966.114
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of dicer-like 1-late flowering phenotype by miR172 expressed by the noncanonical DCL4-dependent biogenesis pathway

Abstract: MicroRNAs (miRNAs) act as down-regulators of gene expression, and play a dominant role in eukaryote development. In Arabidopsis thaliana, DICER-LIKE 1 (DCL1) is the main processor in miRNA biogenesis, and dcl1 mutants show various developmental defects at the early stage of embryogenesis or at gamete formation. However, miRNAs responsible for the respective developmental stages of the dcl1 defects have not been identified. Here, we developed a DCL1-independent miRNA expression system using the unique DCL4-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Loss of function or gain of function of DOG1 decreases or increases, respectively, expression of DICER-related genes (Fig. 4 E-G), and previous studies found that miR156 and miR172 levels are altered in mutants of DCL1, HYL1, SE, TGH, and CDC5 (42,56,58,62,63). However, multiple feedback loops are associated with transcription and processing of miRNAs (41), so further study is needed to clarify the specific mechanism by which DOG1 affects miRNA levels.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Loss of function or gain of function of DOG1 decreases or increases, respectively, expression of DICER-related genes (Fig. 4 E-G), and previous studies found that miR156 and miR172 levels are altered in mutants of DCL1, HYL1, SE, TGH, and CDC5 (42,56,58,62,63). However, multiple feedback loops are associated with transcription and processing of miRNAs (41), so further study is needed to clarify the specific mechanism by which DOG1 affects miRNA levels.…”
Section: Discussionmentioning
confidence: 80%
“…Mutants that are defective in DCL1, HYL1, and SE, all of which are required for miRNA biogenesis (41), display abnormal flowering and alteration in ABA sensitivity of seed germination (54,55). Interestingly, the delayed-flowering phenotype of dcl1-7 mutant could be rescued by expression of a DCL4-dependent MIR839 in which the mature sequence was replaced by the one encoding MIR172, suggesting that the delayed flowering in dcl1-7 plants is a result of the reduction in miR172 (56). Earlier transition from the juvenile to the adult phase was also observed in loss-of-function mutants of SE and HYL1, in association with substantial reduction in miR156, and could be rescued by overexpression of MIR156 (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to DCL1, which is involved in the biogenesis of MIRNA -encoded RNAs, the activity of DCL2-4 is related to the biogenesis of viral short interfering RNA (siRNA) and endogenous siRNA such as retrotransposon siRNA and trans-acting small interfering RNA (Xie et al 2004 ). In addition, DCL4 was recently reported to process some of the “young”, not conserved plant miRNA: miR822, miR839 and miR859 (Tsuzuki et al 2014 ). DCL3 was revealed to cognate dsRNAs and produce the siRNAs that work in RNA-directed DNA methylation (Chapman and Carrington 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant growth‐ The growth conditions of Arabidopsis Dicer‐like 1 mutant and its Landsberg erecta ecotype background (Ler22) were as described . dcl1 ‐ 9 / dcl1 ‐ 9 homozygous mutant plants were distinguished from DCL1 / dcl1 ‐ 9 heterozygous plants or wildtypes by PCR amplification of the octopine synthase terminator sequence of the T‐DNA (portion of the tumor‐inducing plasmid that is transferred to plant cells) by using genomic DNA as a template and the primers 5′‐CTC CGT TCA ATT TAC TGA TTG TAC‐3′ and 5′‐TTG AAT GGT GCC CGT AAC TTT CG‐3.…”
Section: Methodsmentioning
confidence: 99%